K terminologii lyžarského sportu - Arnoštová, D. (Univerzita Karlova v Praze, 2024)
This bachelor thesis focuses on the analysis and lexicographic processing of 53 specialized terms from the field of skiing. The aim of the thesis is to process these terms in accordance with the database structure guidelines of LGCAD. The thesis is divided into a theoretical and a practical part. The theoretical part examines the concept of technical language as well as the principles of terminology. The practical part involves the creation of dictionary entries. The information available in existing dictionaries has been critically analyzed using corpus-based research and subsequently reviewed and refined in collaboration with experts from the field of skiing. The main focus is on the areas of equivalence, morphology, and synonymy. Looking ahead, the scope of processed terms could be expanded, and a specialized German-Czech dictionary for skiing terminology could be developed.